A multi-layered graphene based gas sensor platform for discrimination of volatile organic compounds via differential intercalation - Inanc, Dilce Ozkendir (2023)
Selective and sensitive detection of volatile organic compounds (VOCs) is of critical importance for environmental monitoring, disease diagnosis and industrial applications. Among VOCs, assay development for primary alcohols has captured significant research attention since their toxicity causes adverse effects on gastrointestinal and central nerve systems, resulting in irreversible blindness, and coma, and can be even fatal at high exposure levels. However, selective detection of primary alcohols is extremely challenging owing to the similarity in their molecular structure and characteristic groups. Herein, we have attempted to investigate the differential methanol (MeOH)-ethanol (EtOH) discriminative properties of single-layer, bi-layer, and multi-layer graphene morphologies. Chemiresistors fabricated using the three morphologies of graphene illustrate discriminative MeOH-EtOH responses, which is attributed to the phenomenon of differential intercalation of MeOH within layered graphene morphologies as compared to that of EtOH. This hypothesis is verified by density functional theory calculations, which revealed that the adsorption of EtOH molecules on the graphene surface is more energetically favorable as compared to that of MeOH molecules, thereby inhibiting their intercalation within the layered graphene morphologies. It is further evaluated that the degree of MeOH intercalation increases with increasing layers of graphene for obtaining differential MeOH-EtOH responses. Experimental results suggest possibilities to develop selective and sensitive MeOH assays fabricated using various graphene morphologies in a combinatorial sensor array format.